2018
DOI: 10.1080/15476286.2018.1454250
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of the ribosome associated endonuclease Rae1 and the potential role of conserved amino acids in codon recognition

Abstract: We recently identified a novel ribonuclease in Bacillus subtilis called Rae1 that cleaves mRNAs in a translation-dependent manner. Rae1 is a member of the NYN/PIN family of ribonucleases and is highly conserved in the Firmicutes, the Cyanobacteria and the chloroplasts of photosynthetic algae and plants. We have proposed a model in which Rae1 enters the A-site of ribosomes that are paused following translation of certain sequences that are still ill-defined. In the only case identified thus far, Rae1 cleaves be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 19 publications
0
19
0
Order By: Relevance
“…Although seventeen chloroplastic RNases were predicted by mining the Arabidopsis genome for RNase annotations , this figure certainly needs to be revised. Some predicted RNases were indeed shown to carry other functions (see, for example, the L-PSP/RidA enzyme; Niehaus et al, 2014), and new RNases keep being discovered in bacteria, some of them with a chloroplast homolog awaiting characterization (see, for example, the Rae1/YacP endoribonuclease; Condon et al, 2018). Indeed, as direct evidence of its cyanobacterial origin, nearly all chloroplast RNase homologs are present in bacteria Germain et al, 2013;dos Santos et al, 2018).…”
Section: Plastidial Rnasesmentioning
confidence: 99%
“…Although seventeen chloroplastic RNases were predicted by mining the Arabidopsis genome for RNase annotations , this figure certainly needs to be revised. Some predicted RNases were indeed shown to carry other functions (see, for example, the L-PSP/RidA enzyme; Niehaus et al, 2014), and new RNases keep being discovered in bacteria, some of them with a chloroplast homolog awaiting characterization (see, for example, the Rae1/YacP endoribonuclease; Condon et al, 2018). Indeed, as direct evidence of its cyanobacterial origin, nearly all chloroplast RNase homologs are present in bacteria Germain et al, 2013;dos Santos et al, 2018).…”
Section: Plastidial Rnasesmentioning
confidence: 99%
“…Concerning 5' termini, this might include the roles of the sigma factors that specify PEP initiation sites (112) and other PEP-associated proteins (PAPs; 113), a closer view at RNase J specificity, or a better understanding of some of the numerous factors that have been implicated in rRNA maturation (6). Terminome-Seq would be an excellent choice to gain additional insight into poorly-characterized RNases whose targets have only begun to be described (114)(115)(116).…”
Section: Terminome-seq Of the Pnpase Mutant Points To Its Potential Umentioning
confidence: 99%
“…Until relatively recently, 5 0 -to-3 0 exoribonucleases were believed to be exclusively eukaryotic. However, a bacterial 5 0 -to-3 0 exoribonuclease, RNase J1, was discovered in the model soil-dwelling organism Bacillus subtilis (Mathy et al, 2007) and shown to be widespread in bacteria and archaea (Phung et al, 2013;Condon et al, 2018). RNase J1 is a member of the b-lactamase family of ribonucleases that also possesses endoribonucleolytic activity, at least in vitro (Even et al, 2005).…”
Section: Introductionmentioning
confidence: 99%